Cape gooseberry is ideal fruit for diversification - Singh, D B; Ahmed, N; Lal, S; Sharma, O C; Mirza, A; Pal, A A (Indian Horticulture, 2019)
Looking the potential of cape gooseberry for health and value-added products, its cultivation should be popularized. Then only, we can enjoy this fruit.